LA CAPILLA DE NUESTRA SEÑORA LA SOLEDAD EN LA CATEDRAL DE MURCIA - Pérez Sánchez, Manuel (Imafronte, 1991)
Among the different transformations borne by the Cathedral of Murcia at the end of the 18th. and the beginning of the 19th centuries, it is to point up the construction of the chapel of Nuestra Señora de la Soledad [Our Lady in Her Loneliness], formerly of San Estacio. The chapel was erected between 1807 and 1813, at the request of the Murcian City Council, upon a plan by the architect Don Salvador González, and the architect Don Francisco Bolarín was the director of works. This chapel represents a modest and yet important example of the neoclassical architecture in the region, and one of the finest spaces of the Cathedral, not on because of its excellent proportions, bright lighting and exquisite adornment, but also from its gracefulness and simplicity.